Pemanfaatan Media Sosial Snack Video Sebagai Media Dakwah (Studi pada Akun Snack Video @najwaainunnabi) - Ainunnabilah, Najwa; Subhi, Muhammad Rifa’i (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2024)
The development of the times that is increasingly turbulent in terms of technology and informatics makes Muslims more enthusiastic about spreading da'wah, they must be able to integrate with the changes. This study aims to analysis social changes in the use of social media which is used as a means of da'wah media to spread Islamic messages through mass media, one of which is Snack Video, a video content application. Through the method of study, study and literature, the results of this research show that the Snack Video account of najwaainunnabi conveys an Islamic message about tawadhu’ which is packaged in a language that is easy for the community to understand, such as in interpreting that when we are at the top, there is no need to be arrogant, while when we are at the bottom, do not be humble because Allah is easily able to turn the degree of human beings by turning the times and positions.